Assessment of N/L ratio and subclinical atherosclerosis in FH subjects with or without LDLR mutation. - Barbagallo, Francesco Di Giacomo; Bosco, Giosiana; Marco, Maurizio Di; Scilletta, Sabrina; Miano, Nicoletta; Martedì, Marina; Privitera, Ivan; Papa, Maria Chiara; Piazza, Chiara; Valenza, Francesca (Journal of the Endocrine Society, 2026)
Background Familial hypercholesterolemia (FH) is a genetic disorder characterized by elevated low-density lipoprotein-cholesterol (LDL-C) and increased cardiovascular risk. While the role of LDL-C in atherogenesis is well established, the contribution of inflammatory activation in FH, particularly in relation to genotype, remains poorly defined. We aimed to evaluate the impact of genotype on neutrophil-to-lymphocyte ratio (NLR) and on subclinical atherosclerosis in a cohort of FH subjects. Methods We conducted a cross-sectional study on 423 FH subjects not on lipid-lowering therapy and free from atherosclerotic cardiovascular disease. Biochemical, genetic, and vascular assessments were performed in all participants. The population was divided into 2 groups based on genotype: low-density lipoprotein receptor (LDLR; n = 273) and non-LDLR (NLDLR, n = 150). Vascular profile was assessed by coronary artery calcium score and carotid/femoral plaque presence. NLR was calculated from peripheral blood counts. Results The LDLR group exhibited an higher NLR (2.27 ± 0.86 vs 2.05 ± 0.68, P <.05) than the NLDLR group. LDL-C levels and LDLR genotype were significantly associated with NLR (both P <.05). Multiterritorial plaque involvement was more frequent in the LDLR group than the NLDLR group (P for trend <.05). Age (P <.001), LDL-C (P <.001), smoking status (P <.05), and NLR (P <.05) were independently associated with subclinical atherosclerosis. Conclusion FH subjects with LDLR mutations had a higher NLR and a more severe atherosclerosis distribution. Our findings support the role of NLR as a noninvasive biomarker of early immune activation and highlights the importance of lipoinflammatory status evaluation in FH subjects.